Enculturation of A-Pik (Anti-Senile) Gymnastic Program in Bandung's Elderly Community - Afianti Sulastri; Mustika Fitri; Muhammad Zaky (Universitas Malahayati Lampung, 2023)
ABSTRACT Previous research has shown that A-Pik gymnastics improves cognition in healthy adults. Regular physical activity is related with healthier brains, enhanced memory, more effective planning, and other cognitive abilities, as well as a decreased chance of dementia. The brain continues to generate new cells and synapses throughout life, allowing us to continue learning. This skill is known as